Comparison Of The Image Of The Caring Behavior Of Indonesian Nurses At The Tokubetsu Original Yougoroujin Home Ayumien Tokyo With The Caring Behavior Of Nurses At The Elderly Wisma Marry Home Berastagi 2022 - Mestiana Br Karo; Kristin Valeria Br Barus (Science Midwifery, 2022)
Caring behavior is an action related to the patient's well-being such as sensitivity, comfort, attentive listening, honesty and non-judgmental acceptance. This study was conducted because the researcher wanted to know more about the comparison of the caring behavior of Indonesian nurses at the Tokubetsu Yougoroujin Home Ayumien Tokyo with the caring behavior of the nurses at the Marry Home Berastagi Elderly House 2022. This study aims to analyze the comparison of the caring behavior of Indonesian nurses at Tokubetsu Home. Yougoroujin Home Ayumien Tokyo with caring behavior of nurses at Wisma Marry Home Berastagi 2022. This study used a comparative research method with technique total sampling, the number of respondents at the Tokubetsu Yougoroujin Home Ayumien Home in Tokyo amounted to 48 respondents and at Wisma Marry Home. Berastagi totaled 49 respondents. The research instrument uses that the caring behaviors Indonesian nurse tools questionnaire. The results show that the caring behavior of Indonesian nurses at Panti Tokubetsu Yougoroujin Home Ayumien Tokyo from 48 respondents both 19 respondents (39.6%) and very good as many as 29 respondents (60.4%) and the caring behavior of nurses at Wisma Lansia Marry Home Berastagi from 49 respondents is very good. as many as 49 respondents (100%). Comparison of the caring behavior of Indonesian nurses at Panti Tokubetsu Yougoroujin Home Ayumien Tokyo with caring behavior of nurses at Wisma Lansia Marry Home Berastagi using the independent sample t-test test show p = 000 (<0.05). Therefore, the caring behavior of nurses needs to be improved and maintained to meet patient needs.